An (α,β)- Quadratic Stochastic Operator Acting in S^2 - Jamilov, U.U.; Khudoyberdiev, Kh. O. (Journal of Applied Nonlinear Dynamics, 2026)
In the present paper we consider a family of non-Volterra quadratic stochastic operators depending on the parameters α, β and study their trajectory behaviors. We find all fixed and periodic points for an (α,β)- quadratic stochastic operator on the two-dimensional simplex. A complete description of the set of limit points is given, and we show that such operators have the ergodic property.